Self-Esteem and Family Support with Suicide Risk in High School in Tana Toraja: Self-Esteem and Family Support - Euis Dedeh Komariah; Rosmina Situngkir; Kristia Novia; Felisima Ganut; Joshua Joshua; Wahyudi Anggeng (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Suicide in adolescents has become phenomenal in the Toraja community recently. Suicidal ideation in adolescents is caused by factors of self-esteem and family support. The study aimed to determine the relationship between self-esteem & family support factors and suicide risk in adolescents in Bombongan Village, Tana Toraja Regency. Methods: This study uses quantitative methods with an analytical observational design with a cross-sectional study approach. Sampling using probability sampling technique with a simple random sampling approach with a total sample of 217 respondents Results: The statistical test used is chi-square to determine the relationship between self-esteem and family relationships with suicide risk in adolescents. The results of this study obtained there was a relationship between self-esteem with suicide risk in adolescents with a value of r value = 0.011 and there was a relationship between family support with suicide risk in adolescents with a value of r value = 0.000. Conclusion: The more positive the self-esteem and the better the family support, the lower the risk of suicide in high school teenagers in Bombongan Village.